Burnout and its predictors among pharmacist in government hospitals in Selangor, Malaysia during covid-19 pandemic - Subramaniam, Nivahsshinie (2021)
Pharmacists had been found to be highly susceptible and at risk to burnout. International Classification of Diseases (ICD-11) has classified burnout as an occupational phenomenon. In Malaysia, several local published researches have investigated burnout among healthcare professionals but mostly international studies exist on burnout among pharmacists. Psychological related studies on healthcare workers rarely include pharmacists despite their roles as frontliners during pandemics. An analytical cross-sectional study was conducted to determine the prevalence and predictors of burnout among pharmacists working in government hospitals in Selangor. Pharmacists working in five government hospitals in Selangor were included in this study. Multistage random sampling was used to select the hospitals. Probability proportionate to size technique was used to determine the required sample size from each hospital. The data were collected via email using Google form containing self-administered questionnaires. The questionnaires included socio-demographic characteristics, Copenhagen Burnout Inventory (CBI), Job Satisfaction Survey (JSS), HSE Management Standards Indicator Tool (HSE MS-IT), Generalized Anxiety Disorder-7 Questionnaire (GAD-7), Patient Health Questionnaire (PHQ-9) and Rosenberg Self-esteem Scale (RSES). Data were analyzed using the statistical computer software of SPSS (version 25). Descriptive statistics were conducted to obtain frequency and percentage of variables. Chi square was used to determine the association between variables at level of significance p<0.05. Those variables with p<0.25 were selected for multivariate logistic regression analysis to determine the predictors of burnout. In multiple logistic regression analysis, statistical or stepwise regression technique was used. The results were expressed as odds ratio with 95% CI and two-sided p<0.05 was considered as statistically significant. Model performance was assessed using the area under the Receiver Operating Characteristic curve which measured the model discrimination. Multicollinearity was checked for intercorrelations among the predictors. The response rate was 83% where 312 out of 376 pharmacists completed the questionnaire. In this study, 33 pharmacists (10.6%) had job dissatisfaction and 174 pharmacists (55.8%) had work stress. Approximately 158 pharmacists (50.6%) reported anxiety while 152 pharmacists (48.7%) reported depression. On the other hand, 62 pharmacists (19.9%) had low self-esteem. Prevalence of burnout among pharmacist in this study was reported as 52.9% (Personal), 66.0% (Work-related) and 47.1% (Client-related). The significant predictors of personal burnout based on multiple logistic regression were gender (AOR 2.24, 95% CI 1.29 to 3.89), working hour per week (AOR 2.92, 95% CI 1.60 to 5.32), job satisfaction (AOR 13.00, 95% CI 3.37 to 50.16) and depression (AOR 3.33, 95% CI 1.98 to 5.61). The significant predictors of work-related burnout for male were work stress (AOR 9.10, 95% CI 3.12 to 26.60) and anxiety (AOR 5.91, 95% CI 2.03 to 17.25) while for female were anxiety (AOR 5.91, 95% CI 2.86 to 12.23) and self-esteem (AOR 5.88, 95% CI 1.68 to 20.56). For client-related burnout, working hours per week (AOR 2.44, 95% CI 1.39 to 4.28), job satisfaction (AOR 3.91, 95 % CI 1.49 to 10.27) and anxiety (AOR 2.61, 95% CI 1.57 to 4.32) were the significant predictors. The findings of present study highlighted the prevalence of burnout, association between variables and predictors of burnout. The study successfully concluded gender as one of the significant predictor for personal and work-related burnout, therefore suggested that females were more susceptible to burnout compared to male pharmacists. Those with longer working hour per week were found to have personal and client-related burnout in this study. Pharmacists with job dissatisfaction were also susceptible to personal and client-related burnout compared to those with higher or average level of job satisfaction. Depression and anxiety found to play an important role in burnout. Based on the results reported in this study, pharmacists with depression reported personal burnout and those with anxiety reported work-related and client-related burnout. Besides, work stress and self-esteem were also found to be significant predictors for work-related burnout. Pharmacists with work stress and low level of self-esteem were more susceptible to burnout compared to those without work stress and normal level of self-esteem. Thus, the research questions have been answered and the objectives have also been achieved. This present research reduces the knowledge gap and provided a reference for the topic in Asian context. The results can serve as a baseline to develop an effective module to reduce burnout among the pharmacists.